Suppression of Deactivation Processes in Photocatalytic Reduction of CO2 Using Pulsed Light. Issue 16 (21st July 2016) - Pschenitza, Markus; Meister, Simon; von Weber, Alexander; Kartouzian, Aras; Heiz, Ueli; Rieger, Bernhard
Abstract: The one‐electron‐reduced (OER) species of rhenium‐based catalysts in the homogeneous photocatalytic reduction of CO2 represents the starting point of light‐induced deactivation processes, which lead to low catalyst activity and productivity. Herein, we report the suppression of these processes using pulsed light. Experimental parameters to avoid the irradiation of the OER species were estimated, leading us to conclude that pulse lengths shorter than 1 ns and repetition rates lower than 33 Hz should be employed. [Re(bpy)(CO)3 X] (bpy=2, 2′‐bipyridine; X=Cl (1 ), Br (3 )) catalysts were employed in pulsed irradiation experiments using different light sources, pulse lengths and repetition rates. Pulsed irradiation experiments using LEDs revealed that a minimum average photon flux is necessary to enable CO2 conversion. Furthermore, pulsed laser light with a 10 ns pulse length partially prevented lightinduced deactivation processes, whereas efficient suppression was achieved using a 30 ps pulse length. Abstract : Light and shadow : Pulsed irradiation enables the suppression of light‐induced deactivation processes during the homogeneous photocatalytic reduction of CO2 . Thus, higher catalyst stability and higher turnover numbers are achieved compared to those possible with continuous irradiation.